Influence of semifluorinated alkane surface domains on phase behavior and linear and nonlinear viscoelasticity of phospholipid monolayers - Mielke, Salomé; Tanaka, Motomu (Langmuir, 2020)
Semifluorinated alkanes self-assemble into 30-40 nm-large surface domains (hemimicelles) at the air/water interface. They have been drawing increasing attention to stabilize microbubbles coated with lipids, which are used for enhancing the contrast in sonographic imaging. Although previous studies suggested that semifluorinated alkanes increase the stability of phospholipid membranes, little is known about how semifluorinated alkanes influence phase behaviors and mechanical properties of lipid-coated microbubbles. As a well-defined model of microbubble surfaces, we prepared monolayers consisting of a mixture of phospholipids and semifluorinated alkanes at the air/water interface and investigated the influence of hemimicelles of semifluorinated alkanes on the phase behavior and interfacial viscoelastic properties of phospholipid monolayers. Hemimicelles are phase-separated from phospholipids and accumulate at the phase boundary, which strongly modulates the correlation between solid phospholipid domains. Intringuingly, we found that the mixed monolayer of semifluorinated alkanes and phospholipids possesses linear and nonlinear viscoelastic properties comparable to those of phospholipid monolayers. Since the mixing of semifluorinated alkanes and phospholipids enables one to overcome the intrinsically low stability of pure semifluorinated alkanes against the change in the surface area of microbubbles through the partial dissolution of gas into the aqueous phase, this is a promising strategy for the stable coating of microbubbles in ultrasound diagnosis.
Gesehen am 27.02.2020